Genes & DNA - Walker, Richard, 1951- (Boston, Mass : Kingfisher, 2003)
Genes and inheritance: Variations of a theme -- Discovering genes -- Gene carriers -- New generations -- Gene variation -- Girl or boy? -- Nature or nurture? -- Two of a kind -- DNA: Molecule of life -- Discovering DNA -- Double helix -- DNA at work -- Changing the message -- Human genome project -- DNA, genes, and evolution -- Genetic technology: DNA fingerprinting -- Tracing ancestors -- Genetic engineering -- Screening for diseases -- Gene therapy -- Perfect copies -- Spare parts -- Extinct and endangered -- Predicting the future.
Includes index.
Keywords: Genetics -- Juvenile literature; DNA -- Juvenile literature